Gallbladder Metastasis of Non-small Cell Lung Cancer Presenting as Acute Cholecystitis - Jeong, Yu-Sook; Han, Hye-Suk; Lim, Sung-Nam; Kim, Mi-Jin; Han, Joung-Ho; Kang, Min-Ho; Ryu, Dong-Hee; Lee, Ok-Jun; Lee, Ki-Hyeong; Kim, Seung-Taik (Chinese Journal of Cancer Research; Vol 24, No 3 (September 01, 2012): Chinese Journal of Cancer Research, 2012)
Although non-small cell lung cancer (NSCLC) can metastasize to almost any organ, metastasis to the gallbladder with significant clinical manifestation is relatively rare. Here, we report a case of gallbladder metastasis of NSCLC presenting as acute cholecystitis. A 79-year-old man presented with pain in the right upper quadrant and fever. A computed tomography (CT) scan of the chest and abdomen showed a cavitary mass in the right lower lobe of the lung and irregular wall thickening of the gallbladder. Open cholecystectomy and needle biopsy of the lung mass were performed. Histological examination of the gallbladder revealed a moderately-differentiated squamous cell carcinoma displaying the same morphology as the lung mass assessed by needle biopsy. Subsequent immunohistochemical examination of the gallbladder and lung tissue showed that the tumor cells were positive for P63 but negative for cytokeratin 7, cytokeratin 20 and thyroid transcription factor-1. A second primary tumor of the gallbladder was excluded by immunohistochemical methods, and the final pathological diagnosis was gallbladder metastasis of NSCLC. Although the incidence is extremely rare, acute cholecystitis can occur in association with lung cancer metastasis to the gallbladder.